The Effectiveness of Social Skills Training by Cognitive-Behavioral Group in the Increase of Girls' Self-Esteem and Assertiveness with Addicted Parents - Maryam Esmaeili (Drug Control Headquarters, Research and Education Office, 2011)
Objective: The aim of the study was the survey of social skills training by cognitive behavioral group in the increase of girls' self-esteem and assertiveness with addicted parents in Isfahan. Method: 20 students with addicted parents who had the lowest rate of assertiveness were selected by semi-experimental method in third to fifth grades. Randomly research projects pre-test-post-test control group. Questionnaire to measure assertiveness and assertiveness Gmbryl and Richie Esteem Questionnaire to measure students' self-esteem was used. After the pre-test training program assertiveness over 10 weeks, each week, one session, lasting from one hour and half and at the end of the test was performed after 40 days in both groups re-testing were results using software spss case were analyzed by descriptive statistical methods and two-factor analysis of variance with repeated measures on one factor was used. Results: The results showed that participants in the program and self-assertiveness therapy increased. These results were confirmed in a follow up phase. Conclusion: the training of social skills speeds up assertiveness and self-esteem of students.